Applied Geomatics - Applied Geomatics (Springer Nature, 2026)
The official journal of the Italian Society of Photogrammetry and Topography (SIFET), Applied Geomatics (AGMJ) covers all aspects and information on scientific and technical advances in the geomatics sciences.
FI 0.51
Q2
Keywords: Earth; Space & Environmental Sciences; Geomática; Acuerdos transformativos; Transformative agreements; Ingeniería estructural; Ingeniería mecánica; Topografía terrestre; Tecnología espacial